BAHASA, PRASANGKA, DAN SARA DI MEDIA SOSIAL INDONESIA - A Yusdianti Tenriawali; Taufik Taufik (Kantor Bahasa Provinsi Maluku Utara, 2020)
This study discusses the form and function of language on social media that is considered to contain prejudice and SARA. In social media, language is used as a way of expressing thoughts, so the use of language in social media is full of emotive language. The use of language also has a tendency to be propaganda in social media. It can be positive and negative by using prejudice that serves as a support to influence people who read an article on social media. This research will focus on the analysis of the form and function of languages that is considered containing prejudice and SARA in social media. This is a qualitative descriptive study. The data in this study is texts that contains negative prejudice on Facebook. The research used documentation and note taking technique. The data analysis includes identification, classification, analysis, and inference. The results showed that the form of discourse strategy used on Facebook were comparison, generalization, and the appointment of minorities. The results of the study also showed that all types of discourse strategies tend to show negative prejudice. Meanwhile, the function of the language which is used, namely notifying function and purposing indication.